2006
DOI: 10.1542/peds.2005-1406
|View full text |Cite
|
Sign up to set email alerts
|

Sexy Media Matter: Exposure to Sexual Content in Music, Movies, Television, and Magazines Predicts Black and White Adolescents' Sexual Behavior

Abstract: Exposure to sexual content in music, movies, television, and magazines accelerates white adolescents' sexual activity and increases their risk of engaging in early sexual intercourse. Black teens appear more influenced by perceptions of their parents' expectations and their friends' sexual behavior than by what they see and hear in the media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
338
4
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(370 citation statements)
references
References 28 publications
24
338
4
4
Order By: Relevance
“…18 Brown et al had found that exposure to sexual contact even in music, movies, television and magazines accelerates White adolescents' sexual activity and increases their risk of early sexual intercourse. 19 In this study we found that the duration of watching television has had no significant association with having sexual contact ( p ¼ 0.99) ( Table 6). It is interesting to note that in those watching English movies and serials, there is an increased association of having sexual contact ( p ¼ 0.0002, p ¼ 0.0003), while in those watching cartoons it is significant but negatively associated i.e.…”
Section: Discussionmentioning
confidence: 57%
“…18 Brown et al had found that exposure to sexual contact even in music, movies, television and magazines accelerates White adolescents' sexual activity and increases their risk of early sexual intercourse. 19 In this study we found that the duration of watching television has had no significant association with having sexual contact ( p ¼ 0.99) ( Table 6). It is interesting to note that in those watching English movies and serials, there is an increased association of having sexual contact ( p ¼ 0.0002, p ¼ 0.0003), while in those watching cartoons it is significant but negatively associated i.e.…”
Section: Discussionmentioning
confidence: 57%
“…Previous findings have consistently demonstrated that exposure to sexually explicit content, which causes desensitisation of one's attitudes and values, leads to adolescents' sexually permissive attitudes. (29)(30)(31)(32) Pornography viewing causes adolescents to become stimulated and induces a sexual fantasy about a partner with whom they want to have sex, which in turn influences them to initiate sex when given the opportunity.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Nine longitudinal studies have given potential answers to the question of whether sexy media contribute to early sexual activity, and the answer seems to be "yes." 41,[55][56][57][58][59][60][61][62] Results of 7 of these studies have shown that exposure to sexual content in TV and other media in early adolescenceparticularly for white teenagers-can as much as double the risk of early sexual intercourse. Adolescents whose parents limit their TV-viewing are less likely to engage in early sex.…”
Section: Impact Of Sexual Content On Adolescent Behaviormentioning
confidence: 99%
“…61 The study samples together total nearly 10 000 teenagers nationwide, and the most ambitious studies included other media such as movies, music, and magazines. 57 In addition, a recent study revealed that early exposure to sexual content doubled the risk of teen pregnancy. 60 Clearly, the media play a major role in determining whether certain teenagers become sexually active earlier rather than later, 63 and sexually explicit media may be particularly important.…”
Section: Impact Of Sexual Content On Adolescent Behaviormentioning
confidence: 99%